Choosing Ethnicity, Negotiating Race : Korean Adoptees in America - Tuan, Mia, 1968-; Shiao, Jiannbin Lee, 1970- (Russell Sage Foundation, 2011)
Transnational adoption was once a rarity in the United States, but Americans have been choosing to adopt children from abroad with increasing frequency since the mid-twentieth century. Korean adoptees make up the largest share of international adoptions- 25 percent of all children adopted from outside the United States -but they remain understudied among Asian American groups. What kind of identities do adoptees develop as members of American families and in a cultural climate that often views them as foreigners?